Pancreatic Stones: Treat or Ignore?. (1st August 1999) - Howell, DA
Abstract : Painful, chronic pancreatitis is of complex etiology, but increasing clinical experience suggests that removal of pancreatic duct stones in many cases significantly improves patients' symptoms. The development and refinement of therapeutic endoscopic retrograde choledochopancreatography have permitted improved access to the pancreatic duct, which makes the development of new techniques of stone fragmentation and fragment removal a much more successful nonsurgical intervention. A major step forward has been the understanding of the safety and efficacy of pancreatic sphincterotomy, which is necessary for the removal of these difficult stones. The recognition that extracorporeal shock wave lithotripsy can be delivered safely with good efficacy has revolutionized the nonsurgical management of pancreatic duct stones. Nevertheless, advanced and sophisticated therapeutic endoscopy is necessary to achieve clearance of the duct, which can generally be accomplished in the majority of selected patients. State-of-the-art treatments are described, and some new approaches using pancreatoscopy and electrohydrolic lithotripsy are discussed. Newly recognized long term complications are reviewed. Finally, it must be recognized that chronic pancreatitis is an ongoing disease that does not have a simple treatment or cure, and frequently represents a process of remissions and relapses requiring interventions and problem solving.